EXPONENCIAL DECAY OF WAVE EQUATION WITH A WEAKLY NONLINEAR BOUNDARY DISIPATION AND SOURCE TERM - Cabanillas Lapa, Eugenio (2009)
In this article, we are concerned with the stability of solutions for the wave equation with a weakly nonlinear boundary dissipation and source term. The resultsare proved by means of the potential well method, the multiplier technique and a newintegral inequality.